2016
DOI: 10.1109/tsg.2016.2604286
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Planning in Active Distribution Grids: A Chance-Constrained Optimization with Non-Parametric Probability Functions

Abstract: Abstract-By considering the specific characteristics of random variables in active distribution grids, such as their statistical dependencies and often irregularly-shaped probability distributions, we propose a non-parametric chance-constrained optimization approach to operate and plan energy storage units in power distribution girds. In particular, we develop new closedform stochastic models for the key operational parameters in the system. Our approach is analytical and allows formulating tractable optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Joint expansion planning of energy storage and the distribution grid was modelled by Shen et al [150], Akhavan-Hejazi and Mohsenian-Rad [156] and Iria et al [38]. Shen et al [150] showed that a distribution grid relies on ESS for peak shaving and reliability enhancement.…”
Section: Distribution Level Essmentioning
confidence: 99%
See 2 more Smart Citations
“…Joint expansion planning of energy storage and the distribution grid was modelled by Shen et al [150], Akhavan-Hejazi and Mohsenian-Rad [156] and Iria et al [38]. Shen et al [150] showed that a distribution grid relies on ESS for peak shaving and reliability enhancement.…”
Section: Distribution Level Essmentioning
confidence: 99%
“…Shen et al [150] showed that a distribution grid relies on ESS for peak shaving and reliability enhancement. Akhavan-Hejazi and Mohsenian-Rad [156] took the research a step further by modelling both real and reactive power flows and considering ESS for voltage compensation within an active distribution network. Voltage regulation was also considered by Das et al [147] who took into account both real and reactive power injection by ESS.…”
Section: Distribution Level Essmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with the uncertain output of DGs in the optimization operation in active distribution networks, stochastic programming [15][16][17], chance-constrained based stochastic programming [18][19][20] and robust optimization [21][22][23] have been extensively explored. For example, a multi-scenario framework for optimal power flow under the worst wind scenario and transmission N-1 contingency to properly address the uncertain wind power generation was proposed in [24].…”
Section: Specified Operational Times For Transformer (I J) S Jmentioning
confidence: 99%
“…The process is shown in Figure 9. Then, combined with the approaches of probabilistic optimal power flow [44,60,79], chance constrained programming [62,70], etc., these simulated data of RDGs and load demand could be used in ADS planning models considering high-level uncertainties.…”
Section: Probabilistic Approachesmentioning
confidence: 99%